Total L-carnitine and insulin resistance in non-obese and obese Iraqi women with polycystic ovary syndrome - Maad M. Shallal; Najmah Mahmood; Zina A. Hussein (مجلة كلية الطب, 2023)
Background: Polycystic ovary syndrome (PCOS) is one of the most frequent endocrine illnesses affecting reproductive - age women. L-carnitine has important roles in oxidative stress, energy production and glucose metabolism. It affects insulin resistance as decreased plasma carnitine level has been well reported in type II diabetes mellitus. Hence, it means L-carnitine may reduce insulin resistance which is found in PCO disease.